A Novel Green Synthesis Method of Poly (3-Glycidoxypropyltrimethoxysilane) Catalyzed by Treated Bentonite - Nadia Embarek; Nabahat Sahli (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The present work focuses on the preparation and characterization of poly(3-Glycidoxypropyltrimethoxysilane) (PGPTMS) under mild conditions. Ring-opening polymerization of the 3-Glycidoxypropyltrimethoxysilane (GPTMS) is initiated with the bentonite of Maghnite-H+ (Mag-H+), an ecologic and low-cost catalyst. The evolution of epoxy ring-opening was studied in bulk and in solution using CH2Cl2 as solvent, as well as the influences of several factors such as the amount of Mag-H+, polymerization time and temperature on the yield of polymer were investigated. The best polymer yield (30 %) was obtained in bulk polymerization at room temperature (20 °C) for a reaction time 8 h, and it’s increases with time and reaches 68 % for 7 days. The structures of the obtained polymers (PGPTMS) were confirmed respectively by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR). The thermal properties of the prepared polymers were given by Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA), the Tg of PGPTMS is recorded at -31.27 °C, and it is thermally stable with a degradation start temperature greater than 300 °C, all decomposition stopped at 600 °C. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).